Nursing After Virtue: Revisiting the Work of Derek Sellman - Jantzen, Darlaine (Nursing philosophy, 2026)
Between 1997 and 2009 Derek Sellman published a series of articles that explore the question: what makes a good nurse. To answer this question, Sellman engaged at length with the virtue ethics of Alisdair MacIntyre. Sellman contends that modern nursing is a professional practice, in the sense of practice described by MacIntyre. Based on nursing's ends and moral tradition, therefore, certain professional virtues can be collectively discerned and then nurtured in developing nurses. Contemporary bioethics approaches, including consequentialism, which tend to dominate ethics in nursing, are largely dismissive of virtue ethics. Sellman offers a corrective, proposing MacIntyrean virtue ethics as a solution to the loss of attention to a nurse's character in current ethical theorising within nursing. He proposes the virtues of open-mindedness and trustworthiness as required for nurses to respond to patients and their families or carers; patients, Sellman argues, who are more-than-ordinarily vulnerable. In revisiting Sellman's work, I consider its importance, reflect on the profession's engagement with it, and examine a few of the challenges it presents. Throughout the analysis, I explore MacIntyre's approach in the context of philosophical shifts in the mid-20th century, specifically in relation to moral philosophy and the aretaic turn, and social sciences. The value of contextualising nursing scholars' work in philosophy, and specifically moral philosophy, is presented, with a call to more explicit integration of moral theorising and cognitive science.